Colorectal cancer: from epidemiology to current treatment - Riyad Bendardaf (Libyan Journal of Medicine, 2006)
Colorectal cancer (CRC) was the second most frequent cancer in Europe in 2004, responsible for 13% (376,400) of all incident cancer cases. It is also the second most frequent cause of cancer mortality in Europe, with 11.9% (203,700) annual deaths. When localized, CRC is often a curable disease, but the overall prognosis is determined by the extent of local and particularly metastatic tumour spread. The disease outlook is relatively poor, because advanced disease is a significant cause of worldwide cancer-related mortality. Thus, estimated 5-year survival rates range from nearly 90% in stage I disease (Dukes’ A) to less than 10% in patients with metastatic disease (Dukes’ D). Comprehensive cancer care in the 21st century is dependent on a multidisciplinary approach to patients with malignant disease. Large bowel cancer is no exception, as there is increasing clinical trial data supporting multimodal treatment for both localized and advanced tumours. This review will focus on important aspects in CRC including the latest treatment strategies (chemotherapy, radiotherapy and the targeted therapies).